Health Perceptions Of Leadership Style In Clinic X - Risca Muril Khairani; Dewi Agustina; Nency Utami Br Barus; Rosmala Dewi; Nurna billa; Yulia Rahmadani (Jurnal EduHealth, 2024)
This research focuses on the importance of the leader's role in motivating, directing and developing employees to achieve organizational goals, especially in the clinical context. Factors that influence employee job satisfaction are also in the spotlight, including leadership style, organizational policies, and quality of work life. The research objective to be achieved in this study is to determine and analyze the perceptions of health workers regarding leadership styles at Clinic midwife. Structured interviews were used to explore views and experiences regarding health services at the clinic. The results are understood to gain a deeper understanding of the research subject. The research results show that the leader of Clinic Leaders are also able to control subordinates with a positive approach and show good emotional control in difficult situations. In addition, leaders have a high responsibility in ensuring the quality of service and employee performance meet clinic standards. Based on the results of the interview, the leader of Clinic.